A novel locus in CSMD1 gene is associated with increased susceptibility to severe malaria in Malian children - Damena, Delesa; Barry, Amadou; Morrison, Robert; Gaoussou, Santara; Mahamar, Almahamoudou; Attaher, Oumar; Issiaka, Djibrilla; Dicko, Yahia; Dicko, Alassane; Duffy, Patrick; Fried, Michal (Frontiers in Genetics, 2024)
Background Plasmodium falciparum malaria is still a leading cause of child mortality in sub-Saharan Africa. The clinical manifestations of malaria range from asymptomatic infection to severe disease. The variation in clinical presentation is partly attributed to host genetic factors with estimated narrow-sense heritability of 23%. Here, we investigate the associations between candidate gene polymorphisms and the likelihood of severe malaria (SM) in a cohort of Malian children. Methods Based on our previous genome-wide association studies (GWAS) analysis, candidate genes were selected for in-depth analysis using several criteria including gene-level GWAS scores, functional overlap with malaria pathogenesis, and evidence of association with protection or susceptibility to other infectious or inflammatory diseases. Single Nucleotide Polymorphisms (SNPs) residing within these genes were selected mainly based on p-values from previous severe malaria susceptibility GWAS studies and minor allele frequency (MAF) in West African populations. Results Of 182 candidate genes reported in our previous study, 11 genes and 22 SNPs residing in these genes were selected. The selected SNPs were genotyped using KASP technology in 477 DNA samples (87 SM and 390 controls). Logistic regression analysis revealed that a common intron variant, rs13340578 in CUB and Sushi Multi Domain (CSMD1) gene, is associated with increased odds of SM in recessive mode of inheritance (MAF = 0.42, OR = 1.8, 95% CI = [1.78, 1.84], p = 0.029). The SNP is in linkage disequilibrium (LD) with multiple variants with regulatory features. Conclusion Taken together, the current study showed that an intron variant rs13340578, residing in CSMD1 gene, is associated with increased susceptibility to malaria. This finding suggests that modified regulation of complement may contribute to malaria disease severity. Further studies are needed to identify the causal variants and the underlying molecular mechanisms.